Derechos humanos y libertades democráticas en la ciudad de Tarija – Bolivia - Vásquez Fernández, Bernardino Jesús (2018)
The present work addresses the issue of the exercise of human rights and democratic freedoms in the city of Tarija - Bolivia, in order to determine which are the human rights and democratic freedom that are the most respected and violated, measuring the knowledge about the issue, detecting in this way if there is violation or respect for universal norms, which will allow to generate effective communication policies. The work was done through a survey. The main results indicate that the most violated human rights are: the right of working; right of health; the right to develop that allows a worthy life; right of equality and the right of the environment. It also identifies that the most respected democratic liberties are: freedom of thought, conscience and religion; freedom of peaceful assembly; freedom of opinion and expression. In contrast to less respected democratic freedoms such as: the alternation in power; the holding of periodic and impartial elections and the right of people as a basis of a government authority. As an additional result when comparing the perception between men and women, there is a greater violation of women's rights in issues of: right to security and personal integrity; right to human dignity; right to work; protection and assistance to minors as a family member; right to development that permits a dignified life and the rights of Indian people. Emphasizing significant differences that generate inequalities between men and women in terms of human rights.